PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING TERHADAP PEMEHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 17 PADANG - Afriani, Ira; Zulfaneti, Zulfaneti; Pratiwi, Merina (Pendidikan Matematika, 2013)
Studentâs comprehension of mathematical concept is relatively low for conducting this research. Purpose of this research to determine the students comprehension of mathematical concept by implementing cooperative learning model Snowball Throwing better than students comprehension of mathematical concept that apply to convention teaching of eightth grade student of Junior High School 17 Padang. This type of research is experimental research. The research population was a student of eightth grade at Junior High School 17 Padang. Sampling technique was randomly, selected class is the class VIII1, as experimental class and the class VIII2 as control class. Instrument used is final test with indicator concept of comprehension form of the test used is essaywith totaling 9 item question. Data were analyzed by using a normality test, homogeny test, and t test. Based on the analysis of data obtained by the average result of the students comprehension of mathematical concept experimental was 87.30 and 68.04 the control class student. Hypothesis testing using one side of t-test with MINITAB software, acquired P-value less than , so it can be concluded that the student comprehension of mathematical concept by applying cooperative learning model Snowball Throwing better than student comprehension of mathematical concept that applying conventional learning on student eightth grade at Junior High School 17 Padang.